Current and future distribution of stingless bees in Brazil: identifying potential threats to species conservation - Lima, Valdeir Pereira (2018)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Campus Curitibanos, Programa de Pós-Graduação em Ecossistemas Agrícolas e Naturais, Curitibanos, 2018.